Pelatihan Teknik Pengawetan dan Pengemasan Jamur Merang Segar di Desa Bilabante Kebupaten Lombok Tengah Nusa Tenggara Barat - Rizki Nugrahani; Afe Dwiani; Suburi Rahman; Ni Luh Putu Sherly Yuniartini (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
Mushrooms contain a high percentage of water, causing a shorter shelf life and the quality of the mushroom will decrease rapidly. This fresh mushroom preservation and packaging technique training aims to provide information on wet and dry preservation techniques and how to pack fresh straw mushrooms. The implementation of this activity was attended by members of the Harapan Jaya farmer women's group, Bilebante village, Pringgrata sub-district, Central Lombok district. The training method is to provide material followed by hands-on practice. The training process ran smoothly and was greeted enthusiastically by the participants. This training provides expertise on how to preserve and package fresh straw mushrooms so they can last longer. From the evaluation carried out by the members of the women farmer group, they easily absorbed the material provided and were able to follow well the practices in this training. this can be seen from the results of the discussion and question and answer at the end of the training indicating that the training participants understood what had been done during the training process